Peningkatan Kemampuan Pemahaman Konsep Geometri Siswa SMP Berbasis Software Geogebra - Sopiah, Siti; Sahrudin, Asep; Mauladaniyati, Ratu (Universitas Mathla'ul Anwar Banten, 2024)
This research was carried out based on the problem of students' low ability to understand geometric concepts in mathematics learning, especially in geometry material and the lack of use of learning media. This research aims to: Find out the difference in increasing the ability to understand geometric concepts between students who receive mathematics learning assisted by Geogebra software and students who receive regular learning. The population and sample in this study were students of class VIII SMP Berdikari Cijaku as many as two classes selected by purposive sampling. The instruments used are tests of ability to understand concepts, observation guidelines, and documentation guidelines. Based on the results of data analysis, the conclusion is: There is a difference in the increase in students' ability to understand geometric concepts, where students who receive learning using Geogebra software are better than students who receive conventional learning.